The Influence of Curiosity on Students' Critical Thinking Skills as Viewed from the Perspective of Learning Motivation in Biology Learning on Cell Material - FK Lawal; Hanis Isfa; Norsuhana Abdul Hamid (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the influence of curiosity on students' critical thinking skills as viewed from the learning motivation in biology learning on cell material, in government junior secondary school romin doko, Zaria. Methodology: The research method used is quantitative with an associative survey approach. The sample consisted of 100 students in Government Junior Secondary School Romin Doko, Zaria who were selected through purposive sampling technique. The research instruments were in the form of a curiosity questionnaire, learning motivation, and a critical thinking essay test. Data analysis used inferential statistics using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. Main Findings: The results show that curiosity has a significant effect on critical thinking skills (coefficient = 0.53) and learning motivation (coefficient = 0.48). Learning motivation also has an effect on critical thinking (coefficient = 0.23), and acts as a mediator in an indirect relationship. This model is able to explain 61% of the variation in students' critical thinking skills. Novelty/Originality of this study: This study confirms the importance of strengthening the character of curiosity and learning motivation in improving the quality of students' critical thinking in biology learning.